Kashmiri Identity: A Historical Analysis of Cultural, Religious, and Ethnic Interactions in the Valley - Dr. Nadia Mehrdin; Dr. Aneela saleem; Dr. Javed Iqbal Javed (Corresponding author); Rashida Jabeen; Dr. Ghazanfar Hussain; Dr. Muhammad Tahir (Al-Qanṭara, 2023)
This research paper takes the reader on a fascinating journey into the intricate fabric of Kashmiri identity by providing a thorough historical analysis of the complicated interactions between culture, religion, and ethnicity in the seductive Kashmir Valley. The goal of this research is to unravel the unique and complex personality of this area, which has long been shaped by a wide range of influences. The Kashmir Valley, which is in the northernmost part of the Indian subcontinent, has a colorful and rich history that has greatly shaped the identity of its people. This project attempts to investigate the origins of Kashmiri identity by looking at how cultural, religious, and ethnic linkages have melded over time to define the identity of the people who live in this beautiful region. A qualitative research approach was employed in the study to examine the historical elements of Kashmir's cultural, religious, and ethnic identities. The historical method of this study highlights the complexity of Kashmiri identity, which has been moulded over time by interactions between numerous ethnic groups, faiths, and cultural traditions. Understanding this identity is essential to fostering inclusivity and harmony in the community. Given the coexistence and periodic confrontations between distinct components of identity, communication and reconciliation are crucial to building a more harmonious and inclusive society in Kashmir. To preserve and strengthen the unique Kashmiri identity, steps should be taken to celebrate and protect the region's rich cultural heritage. Interfaith dialogue and community-building projects should be encouraged in order to advance religious harmony. To foster a stronger sense of unity among Kashmiris, it is necessary to accept diversity and value the contributions made by various ethnic groups. Policies that encourage cultural exchange, education, and communication should be given top priority in order to foster future development of a more cohesive and inclusive Kashmiri community.